2022
DOI: 10.3390/vaccines10030481
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Receive COVID-19 Booster Vaccine: Associations between Green-Pass, Social Media Information, Anti-Vax Beliefs, and Emotional Balance

Abstract: The aims of the present investigation were (i) to determine psychological relapses of COVID-19 booster vaccine; (ii) to identify the determining factors affecting willingness to receive COVID-19 vaccine; and (iii) to study the relationship among emotional characteristics (anxiety, stress, depression, optimism), social media information, and the mandatory political choices (i.e., green-pass) in Croatian people. A cross-sectional online survey was conducted for 1003 participants (median age: 40 years) from Croat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 48 publications
2
29
2
Order By: Relevance
“…From a theoretical point of view, our results seem to confirm that the expected effect of subjective norms, and risk perceptions through fear of COVID-19, is mediated by trust in science. Following literature indications [ 14 , 77 , 79 , 94 , 95 , 96 , 97 ], our results also show the role of trust in science as a key factor, able to modulate both the emotional and social factors responsible for the intention to get vaccinated. Indeed, trust in science consistently emerged as a key determinant of adherence to government indications to avoid the spread of SARS-CoV-2 around the world, as several cross-national studies revealed: this has been found to be the case even regarding the most controversial issue, that is, whether to get vaccinated.…”
Section: Discussionsupporting
confidence: 87%
“…From a theoretical point of view, our results seem to confirm that the expected effect of subjective norms, and risk perceptions through fear of COVID-19, is mediated by trust in science. Following literature indications [ 14 , 77 , 79 , 94 , 95 , 96 , 97 ], our results also show the role of trust in science as a key factor, able to modulate both the emotional and social factors responsible for the intention to get vaccinated. Indeed, trust in science consistently emerged as a key determinant of adherence to government indications to avoid the spread of SARS-CoV-2 around the world, as several cross-national studies revealed: this has been found to be the case even regarding the most controversial issue, that is, whether to get vaccinated.…”
Section: Discussionsupporting
confidence: 87%
“…Hence, no influence of the green-pass can be associated with our findings, or to the high vaccination rates reached by the vaccination campaign before July 2021. Additional studies have found that vaccinated people think that a green-pass is useful, while unvaccinated individuals think the opposite [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of two dose recipients willing to receive a third dose of vaccine was somewhat lower than findings from surveys conducted in other countries during the same time period (79-95.5%). (8-10, 21-24) However, more than 15% of respondents in our study reported they remained undecided about receiving a third dose, including over 10% of those who had not yet received any COVID-19 vaccines. Therefore, even in a population with high primary series coverage (almost 90% in our study), there is potential to improve uptake of both primary and additional doses.…”
Section: Discussionmentioning
confidence: 51%